Metode Cerita untuk Mengembangkan Aspek-Aspek Perkembangan Anak - Juhaina, Juhaina (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
The purpose of this research is to find out how the story telling method implemented and how aspects of students’ development of TK Jabal Ilmi developed by using story telling method. This is a qualitative research. That is why the approach used in this research is a qualitative descriptive. Subjects as data sources in this research are teachers and students of TK Jabal Ilmi. Data collection was done by participative observation, questionnaire, and documentation. Data analysis technique was done by data reduction, data display, data conclusion and verification. Finding of this research reveals in the instructional implementation by using story telling method in TK Jabal Ilmi, students started the activities in the morning from line up in front of the class, sing while moving their bodies, pray before the lesson, read iqro, memorize short verses of Qur’an until they have their breakfast together. In the instructional implementation which covers: preparation, material and the way it is delivered, media, until instructional evaluation which occurs there. Effort to develop aspects of students’ development using story telling method covers: moral and religious values, that is teachers tell about universe and recreation, Development of social emotional aspects: teachers tell about the events which often to be seen and felt. In language aspect development using story telling method, students will be trained to listen, read, write, and speak fluently. Cognitive aspect development, students are capable to solve the problem they have, to improve students’ knowledge, to improve students’ memorization, think in logical and symbolic way. On the basis of this research finding, the implementation of storytelling method in the instructional context, teachers pay are required to pay more attention to their students so that the instructional activities can be done well. In order to improve aspects of students’ development, teachers can design the plan which is in line with standard of competencies.